Unusual Lightning Strike Causing Death: A Case report - Amin, Yasin Kareem (Zanco Journal of Medical Sciences (ZJMS), 2025)
In daily autopsies, lightning-related deaths are an uncommon occurrence. Lightning-related deaths are more common in mountainous, wet regions, although they are uncommon in and around Erbil city. Lightning is typically connected to rain, and while lightning-related injuries may be distinguished from electrocution, the latter is also frequently observed. The majority of lightning-related injuries to adults and the elderly are not lethal, but if an individual's strong strike is involved, there may be a tragic outcome. These factors should be investigated in cases of adult fatal lightning deaths. Lightning fatalities are infrequently discussed in medical literature, but since many outdoor workers are implicated, there is a need for more research in this area. Research on lightning deaths in Iraq, a country with a continental, semi-arid, and subtropical climate, needs to focus more on factors of human fatality prevention and treatment. Though more prevalent in adults than in children, an adult death by lightning is documented here. The autopsy results and scene investigation were vital in ascertaining the cause of death.